Featured Article: The ABCDs of Pain Management: A Double-Blind Randomized Controlled Trial Examining the Impact of a Brief Educational Video on Infants' and Toddlers' Pain Scores and Parent Soothing Behavior. (14th November 2017) - Riddell, Rebecca Pillai; O'Neill, Monica C; Campbell, Lauren; Taddio, Anna; Greenberg, Saul; Garfield, Hartley
Abstract: Objectives: To test the efficacy of a brief behavioral pain management strategy (The ABCDs of Needle Pain Management), delivered via video, on infants' and toddlers' pain scores and on parental soothing behavior. Methods: This was a double-blind, parallel trial design. Parent–child dyads ( N  = 128) were recruited before their child's 6-month (infant) or 18-month (toddler) vaccination in a pediatric clinic and randomly assigned to watch a 5-min treatment video or a placebo video. The primary outcome was the Modified Behavior Pain Scale (Taddio et al., Journal of Pain and Symptom Management, 10, pp. 456–463, 1995), coded during four epochs (Pain Reactivity, Pain Regulation 1 min, Pain Regulation 2 min, and Pain Regulation 3 min) after the last vaccination needle. Secondary analyses examined parental use of distraction, rocking, and physical comforting over this same time period. Results: Results demonstrated a treatment effect for toddlers (18-month-olds) for the Pain Regulation 1 ( d  = 0.84) and Pain Regulation 2 ( d  = 0.76) postvaccination scores. Secondary analyses found differences in parental rocking and physical comforting between treatment conditions and between age-groups ( d 's = 0.37–0.54). Conclusions: The ABCD pain management strategy delivered via video was an effective way to reduce toddler pain after vaccination and increase parental use of rocking and physical comforting. The treatment effect was not demonstrated with infants.